Does drainage affect development of heterotopic ossification after total hip arthroplasty?. Issue 10 (October 2022) - Wei, Congcong; Yang, Meng; Chu, Kun; Huo, Jia; Chen, Xiao; Li, Huijie
Objective: To investigate the effect of drainage on heterotopic ossification (HO) after total hip arthroplasty (THA) and to evaluate other postoperative complications and joint dysfunction between patients with and without drainage. Methods: In this retrospective cohort study, the medical records of patients who underwent THA from 2017 to 2019 were reviewed. The patients were divided into a drainage group and non-drainage group. Standard preoperative anteroposterior and lateral radiographs were assessed by senior radiologists for HO analysis. Clinical indicators included the hemoglobin concentration, superficial infection, blood transfusion, hematoma formation, hip range of motion (ROM), erythrocyte sedimentation rate, C-reactive protein concentration, dressing changes, visual analogue scale score, and Harris Hip Score (HHS). Results: The incidence of HO was significantly higher in the drainage than non-drainage group (32.0% vs. 16.3%). The presence of severe HO (Brooker grade III or IV) was also different between the groups. Patients in the non-drainage group had smaller ROM early after surgery, but the final ROM and HHS did not differ significantly between the groups. Conclusions: The rate and degree of HO after THA were significantly different between patients with and without drainage. There is no added advantage of closed suction drainage over no drainage in primary THA.